Strategi Rekrutmen Majelis Taklim Darusshofa Dalam Meningkatkan Jumlah Jamaah - Muhammad Yamin Hasibuan; Rubino Rubino (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2025)
This study aims to analyze the recruitment strategies used by the Majelis Taklim Darusshofa to increase the number of congregants. This study uses a qualitative approach with data collection techniques through in-depth interviews with three key informants: the Chairperson, Secretary, and active members of Majelis Taklim Darusshofa. This technique was chosen to explore first-hand experiences, perceptions, and strategic steps that have been implemented in the recruitment process.The results of the study show that there are three main strategies employed by Majelis Taklim Darusshofa, namely: (1) identifying the needs of the congregants and adjusting the da’wah materials accordingly, (2) utilizing social media platforms such as WhatsApp and Instagram to disseminate information, and (3) intensive personal approaches through direct invitations and attention to the individual conditions of congregants. The findings of recruitment strategies based on social relations, digital, and spiritual needs could be a model for developing sustainable Islamic study groups.